Pemetaan Tiga Dimensi Gua Potro Menggunakan Blender - Suryawan, Arif, Ratnasari Nur Rochmah,ST,MT, Dedi Ari Prasetya,ST (2015)
Caves are natural holes that can be entered by humans, caving in the required knowledge about the cave, the study of the ins and outs of the cave called Speleology, mapping the cave is one part of the science. Map of the caves are usually created and displayed in a two-dimensional picture of the hall has directed, slope angle, length and description of the condition of the state of the cave. The goal of the 3D mapping application using a blender potro caves provide an overview of information systems and virtually explore the cave. Applications are made to provide information to the users while doing explore virtual, 3D applications Caves In Potro are mini-map so that users do not feel puzzled when operating the application. In testing these applications the researchers obtained the test results with questionnaires 93.33% (excellent) for the respondents' assessment of the performance of applications on the computer, so it can be concluded that this application does not take the place of CPU performance and RAM for the application is also portable. Amounted to 90.00% (excellent) in the aspect of the use of this application means that the application can be said to be easy to use. In the aspect of delivery of information received 86.67% (excellent) means that the information provided was good. This app gets 86.67% (excellent) as an attractive appearance in the presentation of the application. This app got a percentage of 90.00% (excellent) in the aspects of interest to use this application in the delivery of knowledge about speology.